Knowledge, Attitude and Practices of Pregnant Women regarding Benefits of Breast Feeding and Immunization in newborns. - Kumail Sajjad; Nafeesa Batool Kazmi; Raheela Rafique; Shakeel Ahmed (Journal of Bahria University Medical and Dental College)
ABSTRACT: Objectives: To study the knowledge attitude and practices of pregnant women regarding benefits of breastfeeding and immunization. Study design: Descriptive cross-sectional study Material and Method: This study was conducted at Department of Obstetrics of P.N.S. Shifa Hospital Karachi over a period of six months. All pregnant women admitted in the obstetric ward were included. After obtaining informed consent participants were administered questionnaire, which was filled in by the researcher. The questions were in the native language. Performa includes questions pertinent to knowledge, attitude and practices regarding benefits of breast feeding and immunization to achieve the millennium development goal 4. Results: Despite of the level of education out of 235 participants at most of them (97%) were aware of role of immunization and breast feeding. But 14.5% lack knowledge of frequency of breast feeding. 42.11% participants said doctor advise her to breast feed while 52.2% counseled by the family lady, midwife and friends. 45.96% participants never got advice by the doctors against use of un-prescribed drugs during pregnancy. Conclusion: The knowledge attitude and practices of pregnant women regarding benefits of breastfeeding and immunization are not upto the mark. There is a need to increase the education of the mothers to ensure better understanding regarding breastfeeding and immunization to achieve the Millennium Development Goal 4.